Genetic association of the tachykinin receptor 1 TACR1 gene in bipolar disorder, attention deficit hyperactivity disorder, and the alcohol dependence syndrome. Issue 4 (9th May 2014) - Sharp, Sally I.; McQuillin, Andrew; Marks, Michael; Hunt, Stephen P.; Stanford, S. Clare; Lydall, Greg J.; Morgan, Marsha Y.; Asherson, Philip; Curtis, David; Gurling, Hugh M. D.
<x xml:space="preserve">Abstract</x> Single nucleotide polymorphisms (SNPs) in the tachykinin receptor 1 gene (TACR1) are nominally associated with bipolar affective disorder (BPAD) in a genome‐wide association study and in several case‐control samples of BPAD, alcohol dependence syndrome (ADS) and attention‐deficit hyperactivity disorder (ADHD). Eighteen TACR1 SNPs were associated with BPAD in a sample (506 subjects) from University College London (UCL1), the most significant being rs3771829, previously associated with ADHD. To further elucidate the role of TACR1 in affective disorders, rs3771829 was genotyped in a second BPAD sample of 593 subjects (UCL2), in 997 subjects with ADS, and a subsample of 143 individuals diagnosed with BPAD and comorbid alcohol dependence (BPALC). rs3771829 was associated with BPAD (UCL1 and UCL2 combined: P = 2.0 × 10−3), ADS (P = 2.0 × 10−3) and BPALC (P = 6.0 × 10−4) compared with controls screened for the absence of mental illness and alcohol dependence. DNA sequencing in selected cases of BPAD and ADHD who had inherited TACR1‐susceptibility haplotypes identified 19 SNPs in the promoter region, 5′ UTR, exons, intron/exon junctions and 3′ UTR of TACR1 that could increase vulnerability to BPAD, ADS, ADHD, and BPALC. Alternative splicing of TACR1 excludes intron 4 and exon 5, giving rise to two variants of the neurokinin 1 receptor (NK1R) that differ in binding affinity of substance P by 10‐fold. A mutation in intron four, rs1106854, was associated with BPAD, although a regulatory role for rs1106854 is unclear. The association with TACR1 and BPAD, ADS, and ADHD suggests a shared molecular pathophysiology between these affective disorders. © 2014 The Authors. American Journal of Medical Genetics Part B: Neuropsychiatric Genetics Published by Wiley Periodicals.